BUFFERED OSMIUM TETROXIDE (OsO(4)) FIXATION FOR CYTOLOGICAL AND FEULGEN MICROSPECTROPHOTOMETRIC STUDIES OF HUMAN RECTAL POLYPS - Leuchtenberger, Cecilie (The Rockefeller University Press, 1955)
Evidence has been presented that when human rectal mucosa and polyps are fixed with buffered OsO(4) according to the method of Palade, staining of paraffin sections by basic and acidic dyes results in a distinct color difference between chromatin and cytoplasm. Furthermore, the Feulgen reaction also can be carried out successfully and such OsO(4)-fixed Feulgen-stained sections are especially suitable for microspectrophotometric determinations of DNA in individual nuclei.